Raman spectroscopy: A prospective intraoperative visualization technique for gliomas - Zhang, Yi; Yu, Hongquan; Li, Yunqian; Xu, Haiyang; Yang, Liu; Shan, Peilin; Du, Yuejiao; Yan, Xiaokai; Chen, Xuan (Frontiers in Oncology, 2023)
The infiltrative growth and malignant biological behavior of glioma make it one of the most challenging malignant tumors in the brain, and how to maximize the extent of resection (EOR) while minimizing the impact on normal brain tissue is the pursuit of neurosurgeons. The current intraoperative visualization assistance techniques applied in clinical practice suffer from low specificity, slow detection speed and low accuracy, while Raman spectroscopy (RS) is a novel spectroscopy technique gradually developed and applied to clinical practice in recent years, which has the advantages of being non-destructive, rapid and accurate at the same time, allowing excellent intraoperative identification of gliomas. In the present work, the latest research on Raman spectroscopy in glioma is summarized to explore the prospect of Raman spectroscopy in glioma surgery.